2010
DOI: 10.1111/j.1439-0272.2009.01032.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of body mass index on seminal oxidative stress

Abstract: Male obesity has been linked with a reduction in sperm concentration and motility, an increase in sperm DNA damage and changes in reproductive hormones. Recent large observational studies have linked male obesity with a reduced chance of becoming a father. One of the potential underlying pathological mechanisms behind diminished reproductive performance in obese men is sperm oxidative stress. The primary aim of this study was to determine if sperm oxidative stress was more common in obese/overweight men. A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
124
0
11

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(140 citation statements)
references
References 46 publications
(60 reference statements)
5
124
0
11
Order By: Relevance
“…Interestingly, there was no association between increased ROS and DNA integrity or sperm motility (Tunc et al 2011), suggesting that elevated ROS may affect other molecular mechanisms that end up by compromising male reproductive health. ROS modulate essential functions of sperm including capacitation, hyperactivation and acrosomal reaction (Fig.…”
Section: Obesity and Male Reproduction R179mentioning
confidence: 95%
See 1 more Smart Citation
“…Interestingly, there was no association between increased ROS and DNA integrity or sperm motility (Tunc et al 2011), suggesting that elevated ROS may affect other molecular mechanisms that end up by compromising male reproductive health. ROS modulate essential functions of sperm including capacitation, hyperactivation and acrosomal reaction (Fig.…”
Section: Obesity and Male Reproduction R179mentioning
confidence: 95%
“…In addition, the rates of azoospermia and oligospermia were also more prevalent in obese men than those in men with normal weight. The authors concluded that the BMI influences the hormonal profile and sperm characteristics, and thus, excess body weight may contribute to subfertility in men (Tunc et al 2011). In another study in 970 patients seeking treatment for nonobstructive azoospermia, overweight men were shown to have worst pregnancy outcomes after microdissection testicular sperm extraction than those with normal weight.…”
Section: Sperm Quality and Obesity-induced Male Subfertility/infertilmentioning
confidence: 98%
“…As increased circulating biomarkers of inflammation are present in patients with MetS, the transmission of the systemic inflammation into the genital tract might be thought to impair semen quality. Nevertheless, only a limited number of studies evaluated seminal tract inflammation in patients with elevated body mass index (BMI) (Lotti et al, 2011;Tunc et al, 2011;Thomas et al, 2013). Two recent meta-analyses assessed a potential association of body weight and sperm quality, one of which revealed no negative effects (MacDonald et al, 2010), while the other reported a twofold increase in the prevalence of azoospermia or oligozoospermia in patients BMI greater 40 (Sermondade et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29][30] Recent evidence from both animal and human studies indicates that male obesity and high-fat diets result in impaired reproductivity, affecting the molecular and physical structure of sperm as well as the health of the developing fetus and subsequent offspring. 27,[31][32][33][34][35][36][37][38][39] In a recent animal study, Rato et al 39 reported that the testicular physiology is sensitive to alterations of whole-body metabolism and that the testicular metabolism can be disturbed by high-energy diets. Disruption of testicular metabolism is associated with decreased sperm quality.…”
Section: Introductionmentioning
confidence: 99%